2018
DOI: 10.1039/c8nj01729h
|View full text |Cite
|
Sign up to set email alerts
|

Au nanoparticle-doped Co3O4–CoFe2O4@SiO2 as a catalyst for visible-light-driven water oxidation

Abstract: Composites of low dielectric constant SiO2, Au and metal oxide was obtained, it showed higher O2 evolution performance due to enhancing the electron transfer rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Lately, as efficient electrocatalysts, cobalt oxides (Co 3 O 4 and CoO) have drawn tremendous attraction due to distinctive features such as their 3D electronic structure, feasible synthesizing methodologies, and efficient catalytic activity [13][14][15][16][17][18][19][20][21]. In spite of this distinctiveness, their poor intrinsic electronic conductivity and inferior bifunctionality for overall electrochemical water splitting have hindered their practical applications [22,23]. To resolve its intrinsic conductivity issue, it was reported while creating oxygen vacancies in these oxides has altered the electronic environment that acted critically to induce conductivity [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, as efficient electrocatalysts, cobalt oxides (Co 3 O 4 and CoO) have drawn tremendous attraction due to distinctive features such as their 3D electronic structure, feasible synthesizing methodologies, and efficient catalytic activity [13][14][15][16][17][18][19][20][21]. In spite of this distinctiveness, their poor intrinsic electronic conductivity and inferior bifunctionality for overall electrochemical water splitting have hindered their practical applications [22,23]. To resolve its intrinsic conductivity issue, it was reported while creating oxygen vacancies in these oxides has altered the electronic environment that acted critically to induce conductivity [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…High-efficiency water oxidation catalysts containing various metal-based oxides have been developed, such as iron, , cobalt, , nickel, copper, manganese, , and so on. Our previous work has been focused on the application of catalysts in typically a [Ru­(bpy) 3 ] 2+ /S 2 O 8 2– /light water oxidation system and has demonstrated superior photocatalytic water oxidation activity using ZIF-67, Co@CoO, and [Co 4 (H 2 O) 4 (HPMIDA) 2 (PMIDA) 2 ] 6– as WOCs. We have confirmed that after the hollow porous Co 3 O 4 –CoFe 2 O 4 nanocubes were modified by SiO 2 and Au nanoparticles, the resulting material showed enhanced water oxidation activity . Sodium persulfate was used for oxidation because of its wide utility as one of the oxidants in the treatment of wastewater to degrade organic pollutants, , providing high solubility, relative stability at room temperature with wide operating pH range (from acidic to alkaline), and its strong oxidizing ability. …”
Section: Introductionmentioning
confidence: 71%
“…So far, the photocatalytic systems are studied mainly in two systems, photosensitizer dye sensitization water oxidation system (such as [Ru(bpy) 3 ] 2+ /S 2 O 8 2À /light WOR system [37][38][39][40]) and semiconductor self-sensitization water oxidation system (such as S 2 O 8 2À /light WOR system [41,42]). Metal oxides and composites [43][44][45], especially Co-based oxides and composites have been extensively applied in photosensitizer dye sensitization water oxidation system due to their remarkable photocatalytic activity and stability and a large part of the researches on water oxidation is of these systems, only a small part is in the semiconductor selfsensitization water oxidation system [46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%